Luzes e sombras na ficção científica: heterotopia e distopia na obra de George Lucas (1971-1977) - Flávio, Lucas Martins (2017)
In literature, some narrative genres both demand and elicit bigger visual dependence: the genres derived from fantasy. It can be said that science fiction, if are not derived from fantasy, shares with it this dependence of a special visuality system. Analyzing the characteristics and peculiarities of this symbol system is important to understand how these narratives create meaning through visual evocation. However, science fiction is not an exclusively literary genre. It is a multimedia genre, sharing this system throughout its history with other narrative platforms such as theater and cinema. In this way, it is also necessary to observe the development of this genre and its transposition to other supports, because the meanings are also constructed historically and socially. Mapping and reflecting on these issues, especially regarding the use of this visual system by George Lucas – and some other directors of the 1970’s – is the basic proposal of this work.